Morphological and molecular identification of the invasive Xylosandrus crassiusculus (Coleoptera: Curculionidae: Scolytinae) and its South American range extending Into Argentina and Uruguay - Landi, Lucas; Gómez, Demian; Braccini, Celina Laura; Pereyra, Vanina Antonella; Smith, Sarah M.; Marvaldi, Adriana Elena (2017)
The occurrence of the exotic “granulate ambrosia beetle” Xylosandrus crassiusculus (Motschulsky) in Argentina and Uruguay is reported for the first time, documenting expansion in South America. Morphological characters are provided to allow distinction of this species from other similar ambrosia beetles. Molecular identification was also done on the basis of the 5′ region of the mitochondrial cytochrome c oxidase I (COI) gene, obtained from a specimen from Argentina and compared with available “barcode” sequences in public databases. Phylogenetic analyses, via maximum likelihood and parsimony, were performed using COI sequences from 17 terminals, including 14 sequences of X. crassiusculus from different continents plus other Xylosandrus and Cnestus species as outgroups. Results from the sequence analyses confirm the identity of X. crassiusculus. The specimen from Argentina and the two sampled from United States showed no differences in their COI sequences. Further studies are needed, on the genetic variation through the native and introduced ranges of the granulate ambrosia beetle, to ascertain the source/s of origin of this biological invasion in the Americas. The present paper reports the expansion of this exotic species in South America into Argentina and Uruguay.